1989
DOI: 10.1002/hed.2880110404
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the skin of the head and neck with perineural invasion

Abstract: This is an analysis of 25 patients with carcinoma of the skin of the head and neck with clinical evidence of perineural invasion, who were managed with curative intent by radiotherapy alone (16) or surgery and radiotherapy (9). All patients had a minimum of 5 years of follow-up. Local control following treatment was observed in 20% of patients treated with radiotherapy alone and 38% of those treated with surgery and radiotherapy. Local control was diminished for recurrent lesions and for tumors that also invad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 13 publications
2
94
1
1
Order By: Relevance
“…21 The results reported by Ampil et al, who performed aggressive surgery with or without XRT for patients with extensive PNI, differed somewhat from the other studies, with a local control rate of 66.7% and 100% 5-and 10-year disease-free survival rates. 26 Later studies, which divided patients into groups with microscopic or extensive PNI, demonstrated that patients who had microscopic PNI had local control rates of 78% to 87% after treatment compared with patients who had extensive PNI (local control rates, 50-55%) 10,16,20,25 (Table 2). Table 3 summarizes local control rates of patients who had SCC with PNI based on their imaging results.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…21 The results reported by Ampil et al, who performed aggressive surgery with or without XRT for patients with extensive PNI, differed somewhat from the other studies, with a local control rate of 66.7% and 100% 5-and 10-year disease-free survival rates. 26 Later studies, which divided patients into groups with microscopic or extensive PNI, demonstrated that patients who had microscopic PNI had local control rates of 78% to 87% after treatment compared with patients who had extensive PNI (local control rates, 50-55%) 10,16,20,25 (Table 2). Table 3 summarizes local control rates of patients who had SCC with PNI based on their imaging results.…”
Section: Resultsmentioning
confidence: 83%
“…10,14,16,20,21,24,25 Patients who underwent MMS with or without XRT achieved superior local control rates of 92% to 100%. 13,15,18,24 Early studies, which consisted almost entirely of patients who were symptomatic or who had imaging-positive disease (ie, clinical PNI) demonstrated local control rates at the lower end of the spectrum, ranging from 38% to 53%, 14,21,24 with 1 reported 5-year survival rate of 33%. 21 The results reported by Ampil et al, who performed aggressive surgery with or without XRT for patients with extensive PNI, differed somewhat from the other studies, with a local control rate of 66.7% and 100% 5-and 10-year disease-free survival rates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations